Optical and electrical characterization of blended active materials for white OLEDs (WOLEDs). (2021) - Gioti, M.; Foris, V.; Kyriazopoulos, V.; Mekeridis, E.; Laskarakis, A.; Logothetidis, S.
Abstract: The purpose of this work is the investigation of white light emission by blending RGB-emitting polymers and the definition of the optimal blending weight ratio, concerning the device operation characteristics and color emission. A comprehensive study of the optical properties and optoelectronic performance of white organic light-emitting diodes (WOLEDs) based on blends of poly(9, 9-di-noctylfluorenyl-2, 7-diyl) (PFO), poly(9, 9-dioctylfluorene-altbaenzothiadiazole) (F8BT) and poly[2-methoxy-5-(3′, 7′-dimethyloctyloxy)-1, 4-phenylenevinylene] (MDMO-PPV) is reported. It was observed that using relatively low ratios, up to 5 wt% of F8BT and MDMO-PPV into the host polymer PFO, slightly affects the dielectric optical response of the blended films and the characteristic electronic absorptions of PFO. Photoluminescence (PL) studies of the blends reveal that the main mechanism is the energy transfer from PFO to F8BT constituent. However, the electroluminescence (EL) study of blends, demonstrates that, in addition to energy transfer, the individual emission of PFO, F8BT and MDMO-PPV leads to a broad emission of the produced OLED devices that covers the whole visible spectral range. As a result, an almost white emission is achieved proving the potentiality to implement such solution-processable blends for lighting applications.